Occurrence of Salmonella and other enteric microbes in faeces of house lizards (Hemidactylus frenatus) - Lo, Gwen; Abdul Aziz, Saleha (Veterinary Association Malaysia, 2013)
Reptiles have been shown to be natural reservoirs of Salmonella and other enteric bacteria and the reptile species close to homes and eateries are house lizards. This study aimed to determine the occurrence of Salmonella in house lizards at residential and eateries premises. Fresh faecal samples were collected from live 25 house lizards and 20 pooled dried droppings were collected around premises. None of the samples were positive for Salmonella. It was probable that a number of lizards may be carrying Salmonella as shown by other previous studies and in this case they were not shedding the bacteria in the faeces at the time and in the dried faecal droppings, Salmonellae was probably absent or did not survive the dry and hot condition. Enteric bacteria that were frequently isolated from fresh droppings were Klebsiella pneumoniae and Citrobacter freundii which were found resistant to amoxicillin + clavulanic and tetracycline.